Development and Preliminary Evaluation of Psychometric Properties of Symptom-Management Self-Efficacy Scale for Breast Cancer Related to Chemotherapy - Shu-Yuan Liang, PhD, RN; Wei-Wen Wu, PhD, RN; Chiu-Ya Kuo, MSN, RN; Yu-Ying Lu, PhD, RN (Elsevier, 2015)
Purpose: The purpose of this study was to develop and preliminarily evaluate the reliability and validity of the Symptom-Management Self-Efficacy Scale-Breast Cancer (SMSES-BC) related to chemotherapy. Methods: The study included three stages. This paper presents the results of stage 2 and stage 3. In total, 34 items in the SMSES-BC were found during stage 1 from qualitative findings, a literature review, and expert suggestions; the 34 items were used for the psychometric properties test. Test-retest reliability and Cronbach α were assessed in the first sample, which included 45 participants for the pilot test (stage 2). The second sample, which included 152 patients, was used to assess the construct validity and concurrent validity (stage 3). Results: The pilot test results revealed a test-retest reliability of .73 (p < .001) and Cronbach α coefficient of .96 for the total scale. Three factors (managing chemotherapy-related symptoms, acquiring problem solving, and managing emotional and interpersonal disturbances) were identified from exploratory factor analysis. Correlation coefficient r was .40 (p < .001), which supported the association between SMSES-BC and the General Self-Efficacy Scale for concurrent validity. Conclusions: The study results demonstrate acceptable reliability and validity for the SMSES-BC that was developed for measuring symptom-management self-efficacy related to chemotherapy for patients with breast cancer. This study suggests further research to validate the construct of the SMSES-BC.